2019
DOI: 10.1007/s11663-019-01600-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rate, Extent, and Mechanisms of Hot Metal Resulfurization with CaO-SiO2-Na2O Slag Systems

Abstract: The resulfurization of hot metal has not been comprehensively studied in literature. This study presents an experimental and mathematical modeling study of resulfurization in thermodynamic and kinetic point of view. The rate, extent, and mechanisms of resulfurization were evaluated by analyzing concurrently the physical properties and sulfur-extracting ability of the slag. Experiments were conducted in a chamber furnace in an argon atmosphere, and the hot metal was sampled with pre-defined basis. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition, in the study of Deo et al, it was observed that by optimizing the learning rate of the backpropagation algorithm, the training result for a sparse data set can be improved. Coupling mechanistic and data‐driven modeling was suggested by Vuolio et al, who studied the possible resulfurization of hot metal via an inverse permanent contact reaction at laboratory‐scale by coupling a simple mechanistic model with ANN. In the study, it was observed that the sulfide capacity of the slag contributed the most to the potential for resulfurization.…”
Section: Mathematical Modeling Of Hot Metal Desulfurization Processmentioning
confidence: 99%
“…In addition, in the study of Deo et al, it was observed that by optimizing the learning rate of the backpropagation algorithm, the training result for a sparse data set can be improved. Coupling mechanistic and data‐driven modeling was suggested by Vuolio et al, who studied the possible resulfurization of hot metal via an inverse permanent contact reaction at laboratory‐scale by coupling a simple mechanistic model with ANN. In the study, it was observed that the sulfide capacity of the slag contributed the most to the potential for resulfurization.…”
Section: Mathematical Modeling Of Hot Metal Desulfurization Processmentioning
confidence: 99%
“…The symbol * means the value is at the equilibrium status. The theoretical value of L S can be calculated as follows [14,15,27,28]:…”
Section: Sulfur Distribution Ratiomentioning
confidence: 99%
“…The symbol means the value is at the equilibrium status. The theoretical value of can be calculated as follows [14,15,27,28]: where is the temperature at the slag-steel interface; stands for the sulfide capacity; and are the oxygen activity and the sulfur activity coefficient in steel, respectively. In this study, the Young’s model [8] is applied to determine the sulfide capacity of slag as shown below:…”
Section: Computational Modelmentioning
confidence: 99%